Diversity of aquatic and terrestrial molluscs from Simeulue Island, with notes on their distribution and some new records - Nova Mujiono; Heryanto Heryanto; Ristiyanti Marsetiyowati Marwoto (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2020)
.